OUTREACH PROGRAM SERVICE PLANNING STRATEGY TO INCREASE LIBRARY INFORMATION ACCESS - Yuliana, Tri; Ritonga, Rohana (Academic Solution Publisher, 2025)
This study explores planning strategies for library outreach programs aimed at enhancing access to information for underserved community. By employing a qualitative descriptive approach, the study highlights the key principles of outreach services planning, including needs assessment, stakeholder collaboration, resource allocation, and program evaluation. The result indicate that tailoring library services to community-specific needs and leveraging technology significantly improve program effectiveness and reach. Collaborative partnerships with stakeholders and efficient use of resources further ensure the sustainability and impact of outreach initiatives feedback, are essential for refining strategies and achieving meaningful outcomes. This article emphasizes the importance of an adaptive and inclusive approach in planning library outreach programs to bridge information gaps, promote lifelong learning, and foster community engagement. Libraries must adopt innovative solutions to overcome barriers and address the dynamic needs of diverse population while maintaining a focus on sustainable and inclusivity.